2017
DOI: 10.1186/s12890-017-0522-3
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and risk factors of moderate to severe obstructive sleep apnea syndrome in major depression: a observational and retrospective study on 703 subjects

Abstract: BackgroundSeveral studies have investigated the prevalence and risk factors of depression in subjects with obstructive sleep apnea syndrome. However, few studies have investigated the prevalence and risk factors for obstructive sleep apnea syndrome in major depression. The aim of this study was to examine the prevalence and risk factors of moderate to severe obstructive sleep apnea syndrome in a large sample of individuals with major depression.MethodsData from 703 individuals with major depression recruited f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(12 citation statements)
references
References 57 publications
(75 reference statements)
1
9
0
2
Order By: Relevance
“…Although a 5-HT immunolabeling alone does not allow conclusive determination of whether 5-HT release was affected, the previously described decrease in 5-HT release in 12N under CIH reinforces this hypothesis (Wu et al, 2017 ). Such a decrease is compatible with observations from clinical and animal studies, leading to the proposition of 5-HT drugs as a potential therapy for OSA (Veasey et al, 1996 , 1999 , 2001 ; Carley and Radulovacki, 1999 ; Nakano et al, 2001 ; Ogasa et al, 2004 ; Saunamäki and Jehkonen, 2007 ; Prasad et al, 2010 ; Zhong et al, 2010 ; Hein et al, 2017 ). This may thus contribute to the lower upper airway muscle tone described in male subjects and male mice than that of females (O'Donnell et al, 2000 ; Jordan et al, 2004 ; Chin et al, 2012 ; O'Halloran et al, 2017 ), because of a decrease in the excitatory influence of 5-HT on hypoglossal motoneurons (Fenik et al, 1997 , 2005 ; Prasad et al, 2010 ).…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Although a 5-HT immunolabeling alone does not allow conclusive determination of whether 5-HT release was affected, the previously described decrease in 5-HT release in 12N under CIH reinforces this hypothesis (Wu et al, 2017 ). Such a decrease is compatible with observations from clinical and animal studies, leading to the proposition of 5-HT drugs as a potential therapy for OSA (Veasey et al, 1996 , 1999 , 2001 ; Carley and Radulovacki, 1999 ; Nakano et al, 2001 ; Ogasa et al, 2004 ; Saunamäki and Jehkonen, 2007 ; Prasad et al, 2010 ; Zhong et al, 2010 ; Hein et al, 2017 ). This may thus contribute to the lower upper airway muscle tone described in male subjects and male mice than that of females (O'Donnell et al, 2000 ; Jordan et al, 2004 ; Chin et al, 2012 ; O'Halloran et al, 2017 ), because of a decrease in the excitatory influence of 5-HT on hypoglossal motoneurons (Fenik et al, 1997 , 2005 ; Prasad et al, 2010 ).…”
Section: Discussionsupporting
confidence: 81%
“…Data in the literature describe the involvement of 5-HT in maintaining appropriate tone of upper airway muscles in animals (Veasey et al, 1996 , 1999 , 2001 ; Carley and Radulovacki, 1999 ; Nakano et al, 2001 ; Ogasa et al, 2004 ; Fenik et al, 2005 ; Zhong et al, 2010 ). Additionally, patients suffering from depression and characterized by 5-HT-system deficiency have a high prevalence of OSA (Saunamäki and Jehkonen, 2007 ; Hein et al, 2017 ). In this context, the observed neuroplasticity of 5-HT systems near hypoglossal motoneurons in male mice may suggest that the repetitive episodes of hypoxia encountered by OSA patients may affect the tone of the upper airway muscles in men, but not women.…”
Section: Discussionmentioning
confidence: 99%
“…Résultats et implications cliniques en rapport avec la 2 e hypothèse du travail doctoral [40][41][42][43][44][45][46][47][48] Dans linsomnie chronique et les sous-types de dépression majeure avec insomnie objective, les altérations polysomnographiques compatibles avec le modèle de lhyperéveil (privation de sommeil et fragmentation excessive du sommeil) sont associées à un risque cardio-métabolique (hypertension artérielle et diabète de type 2) accru ce qui entraîne un risque cardio-vasculaire accru dans ces sous-populations particulières.…”
Section: Hypotheses Resultats Et Implications Cliniquesunclassified
“…The rate of depression among OSA patients ranges from 17% to 41% . Some studies have shown that OSA also occurs frequently among patients with depression . Many studies have reported that the various symptoms that OSA patients complain about are actually related to depression.…”
Section: Discussionmentioning
confidence: 99%
“…3 Some studies have shown that OSA also occurs frequently among patients with depression. 18 Many studies have reported that the various symptoms that OSA patients complain about are actually related to depression. The most typical symptom of OSA, daytime drowsiness, was reported to be more closely related to the presence or absence of depressive mood rather than the degree of OSA based on the AHI.…”
Section: Discussionmentioning
confidence: 99%